The remainder when x 1 9 5 9 − 1 is divided by ( x 2 + 1 ) ( x 2 + x + 1 ) is of the form a x 3 + b x 2 + c x + d .
FInd a + b + c + d .
This is part of the set My Problems and THRILLER
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
@Brian Moehring Brilliant solution.!!!
I just realized I have an error. It's not too hard to fix, but I'm going to bed now, so I'll fix it in the morning...
Log in to reply
Where is the error?
Log in to reply
It wasn't an error in the sense of "this statement is wrong". It was an error in the sense of "this step doesn't always work, but it does in this case". I just had to explain how to jump from a statement about the roots of a polynomial to a statement about polynomial division.
Let ( x 2 + 1 ) ( x 2 + x + 1 ) = k
x 1 9 5 9 − 1 ≡ − x − 1 ≡ x ( x − 1 ) ( m o d x 2 + 1 )
Multiplying throughout by x 2 + x + 1 yields ,
( x 1 9 5 9 − 1 ) ( x 2 + x + 1 ) ≡ x ( x − 1 ) ( x 2 + x + 1 ) ≡ x ( x 3 − 1 ) ( m o d k ) ⋅ ⋅ ⋅ ( A )
Now , x 2 + x + 1 ∣ x 3 − 1 ∣ ( x 3 ) 6 5 3 − 1 6 5 3 = x 1 9 5 9 − 1
⇒ x 1 9 5 9 − 1 ≡ 0 ( m o d x 2 + x + 1 )
Multiplying throughout by x 2 + 1 gives ,
( x 1 9 5 9 − 1 ) ( x 2 + 1 ) ≡ 0 ( m o d k ) ⋅ ⋅ ⋅ ( B )
Combining ( A ) , ( B ) gives ,
( x 1 9 5 9 − 1 ) ( x ) ≡ x ( x 3 − 1 ) ( m o d k )
⇒ ( x 1 9 5 9 − 1 ) ≡ x 3 − 1 ( m o d k )
Hence , a = 1 , b = 0 , c = 0 , d = − 1 ⇒ a + b + c + d = 0
Problem Loading...
Note Loading...
Set Loading...
Suppose ( x 2 + 1 ) ( x 2 + x + 1 ) = 0 . Then either x 2 + 1 = 0 or x 2 + x + 1 = 0 . Now we note:
In either case, we additionally see that x 1 2 = 1 . In other words, every root of ( x 2 + 1 ) ( x 2 + x + 1 ) = 0 satisfies x 1 2 − 1 = 0 . Since we note the former only has simple zeros, we can conclude ( x 2 + 1 ) ( x 2 + x + 1 ) divides x 1 2 − 1 . Therefore, we have shown that x 1 2 ≡ 1 ( m o d ( x 2 + 1 ) ( x 2 + x + 1 ) ) .
Using this, we may write x 1 9 5 9 − 1 = ( x 1 2 ) 1 6 3 ⋅ x 3 − 1 ≡ x 3 − 1 ( m o d ( x 2 + 1 ) ( x 2 + x + 1 ) )
Luckily, this is already reduced! Therefore, a = 1 , b = 0 , c = 0 , d = − 1 and a + b + c + d = 0 .